(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This article examines interactive methods of motivation in elementary mathematics classes, highlighting strategies that enhance student engagement and learning outcomes. Traditional teaching approaches often lead to disengagement, whereas interactive techniques such as game-based learning, collaborative group work, and the use of manipulatives have been shown to foster a more dynamic and student-centered learning environment. Drawing on recent studies and educational research, the article emphasizes the role of these methods in satisfying students’ intrinsic motivation needs and improving academic performance. By integrating interactive tools into their lesson plans, educators can create an engaging atmosphere that not only makes mathematics enjoyable but also cultivates essential problemsolving skills.